KAJIAN FAKTOR LINGKUNGAN DAN IDENTIFIKASI FILUM MOLLUSCA, FILUM ECHINODERMATA DI EKOSISTEM PADANG LAMUN PERAIRAN PANTAI NEGERI TULEHU KABUPATEN MALUKU TENGAH - Stevin Melay; P Tuapattinaya; Fatimah Sangadji (Program Studi Pendidikan Biologi FKIP Unpatti, 2015)
Background: Bodies of State Tulehu a coastal region that has seagrass which adjoins the living marine resources such as mangroves, algae, molluscs, and others. Seagrass in the coastal waters of State Tulehu has spread widely. Information about environmental factors in seagrass ecosystems is still limited that affect its structure. Therefore, to investigate environmental factors and identify the types of phyla phylum molluscs and echinoderms in coastal waters Tulehu village. Methods: The study was conducted in August 2014 by using the quadrant method by using purposive sampling. Hasil environmental research shows physical factors (temperature, pH, salinity, and dissolved oxygen) varies in each quadrant with the results of the identification of Echinodermata and mollusk species also varies. Results: The second research station results obtained 4 types of echinoderms which 1 represents the class Asteroidea species, one species representing Ophiuroidea class, and two types represent the class Echinoidea. On this study, 4 types of echinoderms are divided into three classes, namely class Asteroidea, class Ophiuturoidea, and this Echinoidea. Next class described the types of echinoderms are found on both the research station is Archaster typicus, Ophiocoma erinaceus, Diadema setosum and Laganum depressum. From 3 classes found in both types of Archaster typicus research stations which are found because berhabitat sandy. Conclusion: In the second research station found found four species of the phylum of echinoderms were included in three classes, namely class Echinoidea (sea urchins) are represented by two types, class Asteroidea (starfish) represented by one type and class Ophiuroidea (brittle stars) represented one kind, moreover, In the second research station also found 19 Type molluscs which consists of two types of class Bivalvia and 17 species of the class Gastropoda.